STUDY OF THE EXPERIENCE OF THE SOVIET UNION IN THE MANAGEMENT OF PRODUCTION AND CONSUMPTION WASTE - R. Zh. Sirazhdinov (Вестник университета)
The reform of the system of waste management of production and consumption has been implemented for the third decade, but so far it has not been completed and requires further adjustment of all systems of state and municipal administration in order to achieve the stated goals. The article  examines the historical roots of the system of waste management of production and consumption and its efficiency. The paper analyses the reasons for the  insufficient functioning in Russia of the system of waste management of production and consumption. Improving efficiency requires the development of  new approaches to the development of integrated measures and systemic  solutions that include the full range of incentives, both material and moral.